Acute and long-term effects of gastrin on muscle and bone calcium uptake in rats - Nateetip Krishnamra (2018)
It has previously been proposed that the hypocalcemic action of gastrin was mediated by a gastric peptide gastrocalcin which enhanced bone uptake of calcium (Ca). The present study, thus, aimed to reconfirm the effect of gastrin on muscle and bone Ca uptake and to evaluate a possible direct effect of gastrin on tissue Ca uptake. First, we showed that human and rat gastrin (100μb/100g body weight (bw), s.c.) acutely increased uptake of intragastrically administered 45Ca by the tibia and femur. Interestingly, human gastrin was more effective and also enhanced 45Ca uptake by the gastrocnemius muscle. In order to find out whether gastrin could act directly on bone, 10μg of rat gastrin/100 g bw and 45Ca were injected into the right femoral artery supplying the right leg while the left leg received normal saline and an equal amount of 45Ca. At 30 min, the right gastrocnemius muscle and femur were found to contain 168% and 162%, respectively, more 45Ca than the left leg. In contrast, daily administration of 25 μg of rat gastrin/100 g bw, s.c, for 2 weeks had no effect on muscle or bone total Ca content while the content of 45Ca given on days 12 and 13 was lower in the tibia and femur of gastrin-treated rats. It could be concluded that gastrin transiently enhanced Ca uptake by muscle and bone. However, two-week treatment with gastrin appeared to accelerate the bone turnover rate i.e., enhanced uptake and release of calcium, so that there were no net changes in bone total Ca content at the end of the experimental period. © 1995, Center for Academic Publications Japan. All rights reserved.